A Study of Fall Arrest Fatalities at Construction Site in Malaysia - Bujang Rookey, Dewi Norfitry; Hasmori, Muhammad Fikri (Recent Trends in Civil Engineering and Built Environment, 2021)
Construction fall incidents have significant financial and humanitarian consequences for the construction industry since the construction industry plays a crucial role in economic development, improving safety in the construction sector is very important. In comparison with other types of accidents, fall from height tends to have the highest level of construction incidents relative to other types of accidents. The aim of this study is to investigate the construction safety on fall arrest at the construction site in order to investigate current methods of fall protection, identify issue in their selection use and to produce guidance on best practice for designers and constructors. The method use for this study is quantitative method by sending structured questionnaires to construction industry professionals as targeted respondents and the data obtained will be analyzed using descriptive analysis. As much as 104 construction workers in Malaysia have completed the questionnaires. Based on the findings, main causes of fall from height accidents can be seen in this survey as majority of the respondents strongly agreed that it is important for a construction worker to undergo training in order to stimulate the employee to follow safety regulations. The role of designers and constructors also play a huge role in preventing fall from height at construction site. Risk assessment should also be undertaken in order to determine the degree and duration of workers expose to risk as well as the lack of capability of contractors or sub-contractors can lead to fall from height.  Based from the result, the use of personal protective equipment for construction workers shall be calculated by three separate variables which are awareness, training and experience. Cognitive visualisation of interviews and serious events can be helpful in collection specifics of how fall from height injuries occurred without oversimplifying the issues or sacrificing relevant details.